Risk Analysis of Occupational Health and Safety Using Hazard Identification, Risk Assessment and Risk Control (HIRARC) Method (Case Study in PT Barokah Galangan Perkasa) - Giovanni, Andi; Fathimahhayati, Lina Dianati; Pawitra, Theresia Amelia (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
PT Barokah Galangan Perkasa is a company located in East Kalimantan that is engaged in the manufacturing, repair, and maintenance of ships. The welding activity is the most dominant in shipbuilding, but the implementation of the occupational health and safety (OHS) system is not optimal. There have been several work accidents in the upper accommodation and cargo oil tank areas, such as falling from a height, being hit by welding sparks, and an electrical short circuit. The working conditions in this area are quite risky. Therefore, research on risk analysis is needed. HIRARC is a method for identifying a problem that is assessed at risk based on the likelihood and severity where the results of the assessment can determine the level of risk and give risk control for each work activity. Research results show that there were 40 potential hazards in the upper accommodation area with 77% low risk level, 12% moderate risk level, 8% high risk level, and 3% very high risk level. While in the cargo oil tank area there was 37 potentials hazard with 84% low risk level, 13% moderate risk level, and 3% high risk level. By knowing the risk level, companies can identify work activities that require prioritized improvement. They can also determine appropriate control to prevent the occurrence of such risks. Risk control in the upper accommodation area can be achieved through the implementation of administrative controls, utilization of PPE, and technical engineering controls.